Time-of-Flight Secondary Ion Mass Spectroscopy with Bismuth Primary Ions of Clean and Air-Exposed Surfaces of Tellurium. Issue 6 (December 2014) - Trzyna, Malgorzata; Berchenko, Nicolas; Rading, Derk; Cebulski, Jozef
The regularity of Bi +, Bi 3+ and Bi 3++ primary ions in the time-of-flight secondary ion mass spectroscopy fragment pattern of air oxidized Te and Bi + direct-current scan cleaned Te is discussed. The most intensive fragments for a cleaned Te surface are positive and negative Te x and BiTe x clusters. The sequence of secondary ion cluster formation is Bi-Te alloying followed by sputtering and ionization. For oxidized Te the chemical composition of the produced Te x O y fragments satisfies the relation y = 2 x for positive fragments and y = 2 x + 1 for negative ones. Experimental findings are in a good agreement with the results predicted by Plog's model for TeO2 .